Type II Quadratus Lumborum block for a sub-total gastrectomy in a septic patient - Cardoso,José Miguel (2018)
Abstract Introduction and objectives: Quadratus Lumborum block was recently described and has already shown good results as an analgesic technique in abdominal surgeries, having the potential to significantly reduce opioids consumption and be a valid alternative to epidural catheter. We performed a type II Quadratus Lumborum block for analgesia in a septic patient having a sub-total gastrectomy. Case report: An 80 year-old, ASA III, male patient, weighting 50 kg, with a history of arterial hypertension and hypercholesterolemia, diagnosed with sepsis due to purulent peritonitis was submitted to an open laparotomy. Bilateral ultrasound-guided type II Quadratus Lumborum block was performed before surgery, using 10 mL of levobupivacaine 0.25% and 5 mL of mepivacaine 1%, per side. Pain relief was achieved 5 minutes after injection and the patient referred no pain in the immediate postoperative period. Discussion: Type II Quadratus Lumborum block may be considered a valid alternative for postoperative analgesia in a septic patient undergoing major abdominal surgery with some relative contraindications to epidural catheter placement. It allowed us to achieve excellent pain management avoiding opioids usage. However, more reports are still needed to properly access its usefulness.